A Beginning Bibliography and Sample Curriculum for Teaching Psychoanalysis in the Community. (23rd September 2013) - Twemlow, Stuart; Rudden, Marie G.; Twemlow, Stuart W.; Rudden, Marie G.
ABSTRACT This paper provides suggestions for teaching community based psychanalysis, including references and a course outline. It also attempts a brief historical review of how it has faired as a field in the last several decades. Copyright © 2013 John Wiley & Sons, Ltd.